PERDAGANGAN TERLARANG MENURUT ISLAM DALAM TINJAUAN MAQASHID AL-SYARI’AH - MS, Syaifullah (Hunafa: Jurnal Studia Islamika, 2007)
Basically, in Islam, commerce is allowed unless there is a dalil (religious argument) that bans it. In Islamic perspective, commerce is one of central lives to achieve a piety. Therefore, in Islam, commerce is ethically  regulated  to avoid unfairness from those who involve in it. The purpose is that whoever involves in a commerce must be able to achieve a benefit from it. Even, Islam regulates not only the procedures of commerce transaction  but also the objects of the commerce. This article deals with  commerce banned in Islam based on maqashid al-syaria’h.   Kata Kunci: Perdagangan, tadlis, spekulasi, maqashid al-syari’ah